2020
DOI: 10.1093/jamia/ocaa069
|View full text |Cite
|
Sign up to set email alerts
|

Teledentistry in the diagnosis of oral lesions: A systematic review of the literature

Abstract: Objective The purpose of this systematic review is to summarize information on the use of teledentistry in the diagnosis of oral lesions. Materials and Methods A systematic literature search conducted in August 2018 included articles published until December 2018 in 4 databases. Two reviewers evaluated the search results separately. If they were uncertain as to whether to include an article, a third reviewer made the final de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 24 publications
1
49
0
2
Order By: Relevance
“…Diverse authors suggested the consideration of the use of TD as a practical and innovative strategy to support dental care under specific considerations during the pandemic period (Bizzoca et al 2020; Ghai 2020; Martins et al 2020; Talla et al 2020; Telles-Araujo et al 2020). Many authors highlight the advantages of using TD, including use in the diagnosis and treatment of oral lesions (Ines Meurer et al 2015; Estai, Bunt, et al 2016; Alabdullah and Daniel 2018; Flores et al 2020; Fortich Mesa and Hoyos Hoyos 2020); pathways to improve access to oral health care (Irving et al 2018); validity, cost, and general benefits, as well as uses in clinical practice (Daniel et al 2013; Marino and Ghanim 2013; Estai et al 2018; Teixeira et al 2018; Fortich Mesa and Hoyos Hoyos 2020); and, more recently, the use of teletriage, which is probably one of the most promising uses of TD during the current pandemic (Marino and Ghanim 2013; Ghai 2020). Coincidentally, further research is called for with a focus on the effectiveness, cost-effectiveness, and long-term use of TD to enable evidence-based policy decisions to be made (Estai et al 2018) without affecting the patient–doctor relationship (Fricton and Chen 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Diverse authors suggested the consideration of the use of TD as a practical and innovative strategy to support dental care under specific considerations during the pandemic period (Bizzoca et al 2020; Ghai 2020; Martins et al 2020; Talla et al 2020; Telles-Araujo et al 2020). Many authors highlight the advantages of using TD, including use in the diagnosis and treatment of oral lesions (Ines Meurer et al 2015; Estai, Bunt, et al 2016; Alabdullah and Daniel 2018; Flores et al 2020; Fortich Mesa and Hoyos Hoyos 2020); pathways to improve access to oral health care (Irving et al 2018); validity, cost, and general benefits, as well as uses in clinical practice (Daniel et al 2013; Marino and Ghanim 2013; Estai et al 2018; Teixeira et al 2018; Fortich Mesa and Hoyos Hoyos 2020); and, more recently, the use of teletriage, which is probably one of the most promising uses of TD during the current pandemic (Marino and Ghanim 2013; Ghai 2020). Coincidentally, further research is called for with a focus on the effectiveness, cost-effectiveness, and long-term use of TD to enable evidence-based policy decisions to be made (Estai et al 2018) without affecting the patient–doctor relationship (Fricton and Chen 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, dental practitioners (DPs) can provide dental advice, make provisional diagnosis, and educate their patients over a distance [ 1 , 2 , 3 ]. TD has been applied in different disciplines of dentistry, including but not limited to, preventive dentistry, endodontics, orthodontics, and oral medicine settings, with promising outcomes [ 2 , 4 , 5 , 6 ]. A recent systematic review and meta-analysis of 19 studies found that TD was a very effective means for oral health improvement in terms of prevention and promotion [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another systematic review of 10 studies indicated that TD can successfully be implemented in the diagnosis and detection of dental caries [ 8 ]. The key advantages of TD include cost-effectiveness, providing access to dental care in rural areas and for frail people, reducing wait times, and making referrals in an efficient way [ 5 , 6 , 7 , 8 , 9 , 10 ]. In addition, TD is an opportunity for peer education and consultation through video conferencing, facilitating better dental care for patients [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…A dentist can deliver advice based on patients' information without real-time live contact. 3 A protective physical barrier can be created, making use of teledentistry in COVID-19 surge, a screening protocol can be established where practitioner can conduct the audiovisual examination on a stable patient via video conferencing. Implementation of such programs can be an efficient and cost-effective way to ensure the safety of patient and clinician during the pandemic.…”
Section: Introductionmentioning
confidence: 99%